(untitled) (Research, Society and Development, 2022)
Cervical cancer (CC) is one of the most important types of cancer due to its high incidence and mortality rates among women. Although preventive exams are available for free, low adherence to them still characterizes a public health issue. This study evaluated adherence to cervical cancer screening test (CCST) among university students, outlining the profile of the students who take it to understand the variables that influence its realization or not. A cross-sectional study of a quantitative nature was carried out through the application of a form with the students informed consent. The sample was constituted of female students with sexual life, regularly enrolled in undergraduate courses at the Federal University of Pará. There was a greater tendency to take the CCST among students under 24 years old, in a stable union, in advanced semesters of undergraduate health courses and whose first sexual intercourse occurred under 18 years old. Almost half of them mentioned they did not take the exam often, mainly due to the difficulty to make appointments. We noted there are students who have had a sexual life for more than three years, but have never performed the CCST, which highlighted the need for health education that emphasize the importance of the CCST and publicize the university program to promote students’ health as a valuable tool for expanding test coverage, in addition to the capacity to reduce barriers related to the organization of health services.